Effects of octreotide on responses to colorectal distension in the rat. Issue 5 (1st May 2001) - Su, X; Burton, M B; Gebhart, G F
Abstract : BACKGROUND AND AIMS: It has been suggested that the analgesic effect of the somatostatin analogue octreotide in visceral pain involves peripheral mechanisms. We evaluated the effect of octreotide on responses to noxious colorectal distension in rats. METHODS: In a behavioural study, pressor and electromyographic responses to colorectal distension were evaluated before and after intravenous or intrathecal administration of octreotide. In pelvic nerve afferent fibre recordings, responses of mechanosensitive fibres innervating the colon to noxious colorectal distension (80 mm Hg, 30 seconds) were tested before and after octreotide. RESULTS: Octreotide was ineffective in attenuating responses to colorectal distension in either normal or acetic acid inflamed colon when administered intravenously but attenuated responses when given intrathecally. Administration of octreotide over a broad dose range (0.5 μg/kg to 2.4 mg/kg) did not alter responses of afferent fibres to noxious colorectal distension in untreated, or acetic acid or zymosan treated colons. CONCLUSIONS: In the rat, octreotide has no peripheral (pelvic nerve) modulatory action in visceral nociception. The antinociceptive effect of octreotide in this model of visceral nociception is mediated by an action at central sites.